Practical considerations of embryo manipulation: Preimplantation genetic typing - Garcia, José Fernando [UNESP] (Elsevier B.V., 2001)
In the past years, research in embryo technologies is moving to the establishment of preimplantation genetic typing or also denominated preimplantation genetic diagnosis (PGD). The objectives of these tests are the prevention of genetic diseases transmission and the prediction of phenotypic characteristics, as well as sex determination, genetic disorders and productive and reproductive profiles, prior to the embryo transfer or freezing, during early stages of development. This paper points out the state-of-the-art of PGD, mainly in cattle and discuss the perspectives of multiloci genetic analysis of embryos. (C) 2001 by Elsevier B.V.
Keywords: embryo sexing; PEP-PCR; PGD; bovine; cattle